2011
DOI: 10.4269/ajtmh.2011.10-0256
|View full text |Cite
|
Sign up to set email alerts
|

Low Anticoagulant Heparin Disrupts Plasmodium falciparum Rosettes in Fresh Clinical Isolates

Abstract: Abstract. The binding of Plasmodium falciparum parasitized erythrocytes to uninfected erythrocytes (rosetting) is associated with severe malaria. The glycosaminoglycan heparan sulfate is an important receptor for rosetting. The related glycosaminoglycan heparin was previously used in treatment of severe malaria, although abandoned because of the occurrence of severe bleedings. Instead, low anticoagulant heparin (LAH) has been suggested for treatment. LAH has successfully been evaluated in safety studies and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 41 publications
0
63
0
Order By: Relevance
“…The P. falciparum erythrocyte membrane protein PfEMP1 is present at the surface of infected erythrocytes, and this protein binds to endothelial and cell surface HS in a manner that can be competed out by intravenous injection of modified heparin with minimal anticoagulant activity (Vogt et al, 2006). Low-anticoagulant heparin also disrupts rosetting in fresh clinical isolates (Leitgeb et al, 2011). The interaction between heparin and infected erythrocytes has, unusually, been investigated by single-molecule force microscopy (Valle-Delgado et al, 2013); a binding force in the range 28-46 pN was observed for infected cells, with no binding to noninfected cells.…”
Section: G Interactions Between Heparin and Pathogensmentioning
confidence: 99%
“…The P. falciparum erythrocyte membrane protein PfEMP1 is present at the surface of infected erythrocytes, and this protein binds to endothelial and cell surface HS in a manner that can be competed out by intravenous injection of modified heparin with minimal anticoagulant activity (Vogt et al, 2006). Low-anticoagulant heparin also disrupts rosetting in fresh clinical isolates (Leitgeb et al, 2011). The interaction between heparin and infected erythrocytes has, unusually, been investigated by single-molecule force microscopy (Valle-Delgado et al, 2013); a binding force in the range 28-46 pN was observed for infected cells, with no binding to noninfected cells.…”
Section: G Interactions Between Heparin and Pathogensmentioning
confidence: 99%
“…[22][23][24] Furthermore, heparin of a low-anticoagulant activity (Sevuparin, Dilaforette AB, Stockholm, Sweden) has been shown to dislodge sequestered pRBC into circulation and effectively disrupt rosettes of fresh clinical isolates. 25 The use of Sevuparin as adjunct therapy in severe malaria could, therefore, be beneficial not only because of its antiadhesive properties but also, its HMGB1 binding capacity to reduce inflammation and diminish the overall clinical manifestations.…”
mentioning
confidence: 99%
“…Clinical trials of DF01 (Tafoxiparin) for the prevention and treatment of protracted labour are ongoing [111]. DFX -232 and Sevuparin, as inhibitors of red cell aggregation, known as rosetting, arising from "Plasmodium falciparium" infection, are under clinical trial as anti-malarials and for prevention of vascular occlusion by sickle red cells in severe hereditary anaemia [112].…”
Section: Glycol-split Heparins (Gs-heparins)mentioning
confidence: 99%
“…[99] Astenose Adjuvant in cardiovascular intervention c [113] ROH Heparanase antiangiogenesis inhibitor b [114] ROH P selectin inhibitor [115] LAC-HP antimetastatic b [116] ROH Integrin-melanoma cell binding inhibitor a [117] ROH Antianemic as hepicdine inhibitor b [118] ROH Antinflammation-human elastase inhibitors a [118] gs-LMWH ORG 31733 HIV-1 and HIV-2 inhibitor a [120] SR 80258 Allergic airway response inhibitor b [121] Vasoflux Anticoagulant independent from AT activity, coadjuvant in myocardial infarction therapy d [108,109] NAC from Tinzaparin Antimetastatic b [122] gs-LMWH antimalarial, parasite adhesion, inhibitor b [44] DF01 -Tafoxiparin Labor pain attenuation d [111] M-402 Nocuparanib Metastasis and multiple pathway inhibitor d [110] DFX 232-Sevuparin Antimalarial, distrupting "Plasmodium falciparium" rosettes d [112]]-Preventive activity of vasoocclusion in sickle severe hereditary anemia d S-NACH Anticancer increasing tumor chemo-responsiveness c [35] gs-ULMWH RO-Fondaparinux Antinflammation b [123] Undersulfated RO ST1514" Antinflammatory -heparanase inhibitor b [124] Antiangiogenic, as FGF-2 and VEGF inhibitors b [125,126] N-acylated gs-heparins …”
Section: Conflict Of Interest Statementmentioning
confidence: 99%